TRACING EARLY LITERACY DEVELOPMENT OF ELEMENTARY SCHOOL LOWER GRADES THROUGH RESPONDING TO ILLUSTRATED STORY BOOKS IN INDONESIAN CONTEXT - Hasanah, Muakibatul (IJRDO- Journal of Educational Research, 2016)
The research aims to describe the development of early reading andwriting in lower grade of elementary school students. One way to explore thesedevelopments is through responding to illustrated story books that enable studentsto gain reading and writing in a natural atmosphere. The findings are thedevelopment of early reading and early writing ability in general grows gradually,and appreciation ability of illustrated story books for all grades is relativelyconstant and very good. The implications of the research conclusion are putforward, the teachers in grades 1-3 are expected to create child friendly literacylearning and need to be aware that students’ literacy (especially writing) developsgradually with varying levels of development, therefore, to be more tolerant ofmistakes children made.